Factors affecting Stock Price Behaviour of Commercial Banks in Nepal Stock Exchange - Giri, Dip Bahadur (Journal of Advanced Academic Research, 2024)
This research investigates how factors such as Dividends Per Share (DPS), Earnings Per Share (EPS), Price-Earnings Ratio (PER), and Net Worth Per Share influence the Market Price Per Share of commercial banks in Nepal. The study analyzed the panel data from four commercial banks, consisting of 40 observations, to evaluate the correlation and influence of factors affecting stock price movements. In this study, secondary panel data covering ten years (2070/2071-2079/2080) has been used. Based on the results of this investigation, there is a significant positive correlation between the Market Price Per Share and the Dividends Per Share, Price-Earnings Ratio, and Net Worth Per Share but a negligible effect of Market Price Per Share and Earnings Per Share of commercial banks.